Identification of Transposable Elements in Conifer and Their Potential Application in Breeding. (June 2020) - Wang, Junhui; Lu, Nan; Yi, Fei; Xiao, Yao
Transposable elements (TEs) are known to play a role in genome evolution, gene regulation, and epigenetics, representing potential tools for genetics research in and breeding of conifers. Recently, thanks to the development of high-throughput sequencing, more conifer genomes have been reported. Using bioinformatics tools, the TEs of 3 important conifers ( Picea abies, Picea glauce, and Pinus taeda ) were identified in our previous study, which provided a foundation for accelerating the use of TEs in conifer breeding and genetic study. Here, we review recent studies on the functional biology of TEs and discuss the potential applications for TEs in conifers.